That distant land eaudiobook 23 short stories. - Berry, Wendell (Port William., 2010)
That Distant Land collects twenty-three stories, interlinked with each other and with the other published "Port William" novels. The stories, arranged in their fictional chronology (from 1888 to almost the present day), become one sustained work, a new novel that spans the entire life and time involved. The range of this book is extraordinary - it offers rest for the weary, hope for the beleaguered, and strength for everyone else.